Medycyna stylu życia jako prozdrowotny trend współczesnego prosumenta - Czerska, Iwona; Trojanowska, Angelika; Korpak, Tetiana (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The aim of this study is to present the profile of the modern prosumer and analyze their behavior on the health services market in the context of the latest health-promoting trend — lifestyle medicine. The patient’s participation in medical diagnostics was discussed. Attention was paid to the reasons for transformation of medical systems, among others due to changes in the patient’s needs. The theoretical aspects of lifestyle medicine, including evidence-based medicine (EBM), were discussed. Finally, an analysis of the lifestyle of Polish consumers was made based on the results of own study. Less than 20% of respondents are familiar with the term “lifestyle medicine”. Most respondents identify this term with a healthy lifestyle. The respondents’ declarations show that the modern consumer leads a healthy lifestyle, regularly engaging in sports and eating properly balanced meals. As an informed consumer, he or she reads the labels on the packaging and considers each purchase very carefully. He or she is also vulnerable to advertising and other marketing tools, and is aware of this. Nearly 61% of respondents do not know the term “prosumer”. For other people, aprosumer is the modern consumer who consciously and actively makes choices, is involved in co-creating the product and takes part in its promotion.
Keywords: lifestyle medicine; prosumer; EBM